A simple immunoenzymatic method for measuring IgE in human sera. - Gluesdon, J L (1976)
A reliable and relatively simple method for the estimation of serum IgE by single radial immunodiffusion is described. The method requires glucose oxidase-labelled antibodies. The method permits the measurement of IgE concentrations ranging from 20 to 700 i.u./ml. The values obtained in unknown samples were in good agreement with those obtained by radioimmunoassay (correlation coefficient r=0-9557).